The Indonesian Ulema Council Fatwa Analysis on The Environment and Their Relationship to The Green Economics Concept Development - Iiz Izmuddin; Rusyaida Rusyaida; Gusril Bashir; Pendi Hasibuan; Awaluddin Awaluddin (Jurnal Syntax Admiration, 2022)
The Majlis Ulama Indonesia is an independent institution tasked with providing answers to religious and social issues of the people. As an independent institution, the MUI has the responsibility to issue fatwas that can promote the benefit of society and the environment so that shared prosperity can be realized. At this time the MUI has issued a Fatwa on the environment which aims to protect and maintain the sustainability of the existing ecosystems in every community environment. Of course this needs to be analyzed whether the MUI fatwa has met the sustainability aspects and its linkages with green economic aspects as a measure of environmental welfare. The methodology used in this research is qualitative with a content analysis approach, (literature study), namely by analyzing the books and fatwas related to this research, so that conclusions can be obtained. The results of this study indicate that the method and analysis of environmental sustainability in MUI fatwas related to the environment have used methods that are commonly used so far, while the contents of the fatwa are related to sustainability of the existence of ecosystems and the environment, but MUI's arguments have not included the latest research results. about the environment. MUI fatwas related to the environment have accommodated green economic principles as seen in the general provisions contained in the fatwa decisions.